The effects of job demands and job resources on work stress among administrative staff at College of Business, Universiti Utara Malaysia, Kedah - Nur Hazirah, Md Yusof (2017)
Employees stress is one of the important issues that need to be addressed by every organization and also for researchers in order to understand their impacts on employees and organization. Presently, employees stress is a challenge that many organizations struggle to overcome. Thus, to gain better understanding, this study identifying the factors that influence work stress. The main purpose of this study is to examine the effects of job demands and job resources on work stress among administrative staff at College of Business, Universiti Utara Malaysia, Kedah. Job demands were measured through element of workload and role conflict. Meanwhile, job resources were measured by supervisor support and co-worker support. For data collection, about 70 set of questionnaire was distributed to administrative staff with grade 11 to 38 from College of Business, Universiti Utara Malaysia (UUM), Kedah. Then, the data were analyzed by using IBM SPSS version 20. The result gain through analysis of Pearson correlation and Multiple regression indicated that role conflict and workload has positive relationship with work stress. These finding provides useful information to the management at UUM regarding their employees’ well-being and concerning. Besides that, it helps to enhance the underpinning theory in this study that is Job Demand-Resources model.